2014
DOI: 10.1158/1541-7786.mcr-14-0302-t
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Inhibits Tumor Cell Invasion via Receptor-Independent Mechanisms

Abstract: Extracellular adenosine mediates diverse anti-inflammatory, angiogenic, and other signaling effects via binding to adenosine receptors, and it also regulates cell proliferation and death via activation of the intrinsic signaling pathways. Given the emerging role of adenosine and other purines in tumor growth and metastasis, this study evaluated the effects of adenosine on the invasion of metastatic prostate and breast cancer cells. Treatment with low micromolar concentrations of adenosine, but not other nucleo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Importantly, these effects of adenosine were well within the adenosine concentration range that has been measured in the tumor microenvironment [48]. In line with these findings, Virtanen et al recently described an inhibitory effect of exogenous adenosine on cancer cell invasion and migration [18]. They suggested that receptor-independent mechanisms were responsible for this effect.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Importantly, these effects of adenosine were well within the adenosine concentration range that has been measured in the tumor microenvironment [48]. In line with these findings, Virtanen et al recently described an inhibitory effect of exogenous adenosine on cancer cell invasion and migration [18]. They suggested that receptor-independent mechanisms were responsible for this effect.…”
Section: Discussionsupporting
confidence: 63%
“…Cells were cultured for a maximum of 15 passages to minimize the risk of experimental variance due to mutations. This is particularly important as there are contradictory reports about the expression levels of adenosine receptor subtypes in breast cancer cell lines [18][19][20]. Prior to experiments, the cells were trypsinized and washed once with serum-containing medium and three times with serum-free medium containing 20 mM HEPES and 0.1 % bovine serum albumin (BSA).…”
Section: Cell Culturementioning
confidence: 99%
“…Moreover, the effect of the dCF on tumour invasion and migration was also clearly visible in more invasive human breast cancer cells, MDA‐MB‐231 and T47D. It has been shown previously, that this could be a receptor‐independent effect mediated by adenosine via inhibition of AMP‐activated protein kinase . However, based on our study, the significant role of adenosine receptors in these processes should also be noticed.…”
Section: Discussionmentioning
confidence: 99%
“…In meduloblastoma cell lines, the metastatic potential is inversely correlated with CD73 expression and activity [35]. Pharmacological inhibition of CD73 reduces adhesion but increases the invasion/migration capacities in vitro [17, 36], and treatment with adenosine (produced by CD73) inhibits cell migration and invasion [37]. More recently, loss of CD73 has been involved in epithelial barrier misstructuration and endometrial tumor progression [17].…”
Section: Discussionmentioning
confidence: 99%